The English Grammatical Speaking Errors of Sasakness Learners: A Case Study at English Literature Students - Panji Tanashur; Nuralfi Lail; Erwin Suhendra (Humanitatis : Journal of Language and Literature, 2024)
The need for learning English as a foreign language is rising due to the interconnectedness of today's globe, where English is the universal language of academics, commerce, entertainment, and culture. This has raised interest in the automatic approach to evaluating spoken language competency. In this sense, learning grammar is one of the most important components of language competency. This study aims to analyze the grammatical speaking errors made by the second-year Universitas Bumigora students learning English as a foreign language in the Speaking 3 course. The methodology involves a qualitative research design using the surface strategy taxonomy to analyze and classify the data collected from 20 English literature students. The errors are categorized into omission, addition, disordering, and selection. The types of errors identified include plural and singular nouns, subject-verb agreement, part-of-speech word orders, regular and irregular verb usage, and word order. Data were obtained through two cycles; in the first cycle, the participants receive feedback on their errors, and their insight on the errors is also considered in cycle 2. Data analysis on both cycles reveals that there were significant errors in singular and plural pronoun usage of above 20%; the subject-verb agreement has an increasing percentage of errors (4.16%) after being given feedback on the first cycle; part of speech has significantly lower errors (8.03% and 1.09%); the usage of articles is similar to subject-verb agreement errors, there was slight increasing percentage of errors (1.8% and 0.20%). Thus, the data revealed that learners are significantly influenced by both the interference of their first language and the challenges inherent in acquiring a second language. Therefore, errors in spoken articulation still existed, though learners were able to comprehend the grammar in written text.